Analysis of neutron-temperature oscilations in neutron multiplying systems with delayed neutrons - Vodyanitskii, A.A.; Rudakov, V.A. (Вопросы атомной науки и техники, 2011)
External sources with a given frequency excite neutron and temperature oscillations. Analytical treatment and analysis of oscillations were performed under conditions of both the weak coupling and strong coupling between the oscillation branches.The neutron oscillation branch describes the wave propagation along the coolant flow with amplitude rising in the range of high flow velocity and with amplitude decreasing in the range of low velocity and high frequencies, as well as, the oscillation propagation in the opposite direction. The temperature oscillations undergo a weak decrease of amplitudes. The strongly coupled neutron-temperature oscillations are excited, as the microscopic fission cross-sections are dependent on the "effective" temperature of thermal neutrons.The influence of delayed neutrons is studied. Comparison between the analytical treatment data and the analysis of experimental measurements confirms these conclusions. Зовнішні джерела з заданою частотою в нейтронній розмножувальній системі збуджують нейтронні і температурні коливання. Проведено аналітичний розгляд і аналіз коливань в умовах як слабкjого, так і сильного зв'язків між гілками. Нейтронна гілка коливань описує їх розповсюдження уздовж течії теплоносія з наростанням амплітуди в області великих швидкостей його руху, а також, з затуханням амплітуди - в протилежному напрямку. Конвективна гілка температурних коливань зазнає слабкого затухання амплітуди. При залежності мікроскопічних перетинів поділу ядра від температури теплових нейтронів збуджуються сильно зв'язані нейтронно-температурні коливання. Враховано вплив запізнілих нейтронів. Аналітичний розгляд і аналіз експериментальних вимірювань підтверджують ці висновки. Внешние источники с заданной частотой в нейтронной размножающей системе возбуждают нейтронные и температурные колебания. Проведены аналитическое рассмотрение и анализ колебаний в условиях как слабой, так и сильной связей между ветвями. Нейтронная ветвь колебаний описывает их распространение вдоль течения теплоносителя с нарастанием их амплитуды в области больших скоростей его движения, а также с затуханием амплитуды - в противоположном направлении. Конвективная ветвь колебаний испытывает слабое затухание амплитуды. При зависимости микроскопических сечений деления ядер от температуры тепловых нейтронов возбуждаются сильно связанные нейтронно-температурные колебания. Учтено влияние запаздывающих нейтронов. Сравнение аналитического рассмотрения с анализом экспериментальных измерений подтверждает эти выводы.